2019
DOI: 10.1021/acsbiomaterials.9b00604
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hybrid Hydrogels from Silk Fibroin and Tannic Acid with Enhanced Gelation and Antibacterial Activities

Abstract: The development of silk fibroin hydrogels with a suitable gelation rate and mechanical strength, as well as multifunctional properties including injectability, antibacterial activity, and adhesiveness, is of importance for wound healing and skin infection treatment, yet their design remains challenging. Herein, a multifunctional hydrogel from silk fibroin and tannic acid is developed, relying on the favorable interactions between them. The hybrid hydrogel (SF-TA) exhibits numerous advantages, such as short gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 55 publications
4
93
1
Order By: Relevance
“…For example, the injectable, biodegradable and biocompatible hydrogels, which can respond to both pH and physiological temperature, are more suitable for the tumor treatment by the targeted drug release 110 . The hydrogels with optimal mechanical strength, injectability, antibacterial activity and adhesion are the ideal choice for wound healing and skin infection treatment 81 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the injectable, biodegradable and biocompatible hydrogels, which can respond to both pH and physiological temperature, are more suitable for the tumor treatment by the targeted drug release 110 . The hydrogels with optimal mechanical strength, injectability, antibacterial activity and adhesion are the ideal choice for wound healing and skin infection treatment 81 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of growth factors, cytokines and drugs to biologically functionalize the SF hydrogels 5 , the development of the hydrogels with specific adhesion with the wound is also an effective method to improve the functionality of the SF-based wound dressings 112 . In a related study, Juan Jing et al 81 reported a SF hydrogel with adhesive properties. The hydrogel possessed both antibacterial and antioxidant activity.…”
Section: Wound Healingmentioning
confidence: 96%
See 1 more Smart Citation
“…Tannic acid was used to form a complex with silk by non-covalent interactions. Gel-like forms based on silk fibroin cross-linked by tannic acid showed improved wet-adhesive properties and stability [ 71 , 72 ]. TA and silk sericin may be conjugated via hydrogen bonding interactions.…”
Section: Tannic Acid-based Biomaterialsmentioning
confidence: 99%
“…Jing et al . [ 13 ] reported a (Tannins Acid) TA gelatin-enhanced SF–TA hybrid hydrogel based on a chemical crosslinking method which exhibited remarkable antimicrobial and antioxidant activities for improving wound healing.…”
Section: Introductionmentioning
confidence: 99%